Implementation of the Zero Waste Concept to Improve Kitchen Operational Efficiency at Elkartika Hotel Batu Malang (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2026)
This study examines the implementation of the zero-waste concept in the kitchen operations of Elkartika Hotel Batu Malang and evaluates its impact on operational efficiency. A descriptive quantitative approach was employed, with data collected through observations, interviews, documentation, and questionnaires distributed to respondents directly involved in kitchen activities. The primary data source consisted of hotel kitchen employees, while the secondary data were obtained from relevant documents and literature. Data were analyzed using descriptive statistics, including mean scores and percentage calculations. The findings indicate that the implementation of the zero-waste concept at Elkartika Hotel Batu Malang is highly effective, achieving a mean score of 4.93 and a percentage of 98.6%, which falls within the “Very Good” category. Kitchen operational efficiency also demonstrated excellent performance, with a mean score of 4.86 and a percentage of 97.2%. The successful implementation of the zero-waste concept is supported by several practices, including process optimisation, proper waste management, improved resource utilisation, adherence to the First In, First Out (FIFO) system, and the effective management of kitchen raw materials. The results further reveal a positive relationship between zero-waste practices and kitchen efficiency, reflected in improved productivity, enhanced work quality, reduced food waste, and lower operational costs. These findings suggest that adopting zero-waste principles can serve as an effective strategy for promoting sustainable hospitality practices and improving operational performance.